Addressing Water Scarcity in Samdrupjongkhar Thromde, Bhutan: Feasibility Study and Design of a Sustainable Gravity Water Supply System - Sharma, Vasker; Tamang, Phurba; Tenzin, Rigden Yoezer; Tshering, Dawa (Archives of hydro-engineering and environmental mechanics, 2023)
The provision of a reliable water-supply system is essential for the development and well-being of urban communities. Samdrupjongkhar Thromde, located in Bhutan, has been facing water supply challenges despite the presence of a water treatment plant. The non-perennial nature of the current water source coupled with malfunctions in water pumps has led to acute water shortages in the municipality. To address this issue, this study carried out a feasibility investigation and designed a gravity water supply system by conducting an EPANET (Environment Protection Agency Network Evaluation Tool) analysis. The study involved field visits to identify potential water sources, and a topo-graphic survey using RTK (Real Time Kinematics) technology to determine the optimal pipeline route. The EPANET analysis was then conducted to evaluate the hydraulic performance of the initial route. Based on these findings, a final water pipeline route was selected considering factors such as terrain characteristics, construction feasibility, avoidance of negative water pressure, and minimum encroachment of private land. The results showed that the maximum pressure head within the pipeline system reached 296 m with a maximum water flow velocity of 5 m/s. However, at the outlet, the pressure head decreased to 70 m and the velocity decreased to 2 m/s. Two Break Pressure Tanks (BPT) were strategically placed to achieve this pressure reduction. The chosen pipe materials and their placement ensure the long-term reliability and functionality of the water supply system, while considering maintenance convenience and terrain characteristics.